2009
DOI: 10.1093/molehr/gap058
|View full text |Cite
|
Sign up to set email alerts
|

An RNA spiking method demonstrates that 18S rRNA is regulated by progesterone in the mouse uterus

Abstract: Identifying suitable housekeeping genes for quantitative RT-PCR in the uterus is problematic, as this tissue undergoes significant structural and functional alterations during the oestrous cycle and pregnancy in response to circulating hormones. The suitability of 18S rRNA as a housekeeping gene in mouse uterus was investigated by introducing an 'RNA spike' standard into the reverse transcription reaction. 18S rRNA levels increased by Day 4 of pregnancy and after progesterone administration in ovariectomized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Each cDNA master-mix reaction contained an equal amount of in vitro-transcribed RNA spike and a 300-bp region of the T7 promoter region of the pBluescript phagemid ). This spike controls for the efficiency of the cDNA reaction (Craythorn et al 2009;Winnall et al 2009). Following cDNA synthesis, samples were diluted 1 : 10 in nuclease-free sterile water.…”
Section: Quantitative Rt-pcr (Qrt-pcr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Each cDNA master-mix reaction contained an equal amount of in vitro-transcribed RNA spike and a 300-bp region of the T7 promoter region of the pBluescript phagemid ). This spike controls for the efficiency of the cDNA reaction (Craythorn et al 2009;Winnall et al 2009). Following cDNA synthesis, samples were diluted 1 : 10 in nuclease-free sterile water.…”
Section: Quantitative Rt-pcr (Qrt-pcr)mentioning
confidence: 99%
“…Messenger RNA from PND0 FSKO mice, ovarian tissue from adult WT mice and human myometrium were included as internal controls. The RNA spike was used to normalise the data (Craythorn et al 2009;Winnall et al 2009) and was detected at the same level in each tissue (data not shown). Utilisation of spike was particularly important for investigations of the oestrous-cycle stage as housekeeping genes, such as 18S, are influenced by steroid hormones (Craythorn et al 2009).…”
Section: Quantitative Rt-pcr (Qrt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue samples were processed and assessed for mRNA expression levels using established methods, which have been described in detail previously (6,41). All tissues for mRNA measurements were stored at [minus]80°C.…”
Section: Rna Extraction Cdna Synthesis and Quantitative Rt-pcrmentioning
confidence: 99%
“…For each tissue cDNA, a nonreverse-transcribed control was produced to act as an internal negative control. A phagemid-derived RNA "spike" was added to each reaction as an external standard control, as previously described (6,41).…”
Section: Rna Extraction Cdna Synthesis and Quantitative Rt-pcrmentioning
confidence: 99%